Common beans Kenya: Climate risk assessment - Duku, Confidence; Groot, Annemarie; Demissie, Teferi Dejene; Muhwanga, Joseph; Nzoka, Oscar; Recha, John W.M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Kenya is the seventh biggest producer of common beans globally and the second leading producer in East Africa (KenInvest, 2016). Beans rank second to maize in importance as a food crop. They are cultivated almost exclusively by about 1.5 million smallholder farmers on about a million hectares, with yields of about 0.6MT/ha. The main producing areas for dry beans include the Rift Valley, Eastern, Lake Victoria zone, Western and Central regions that account for 33%, 24%, 18%, 13% and 20% respectively of national production. National consumption is assessed to be about 755,000MT annually against a production of about 600,000MT a year. Per capita consumption is estimated at 14 kg per year, but can be as high as 66 kg per year in the country’s western regions. Bean production has been declining in Kenya, from 714,492 tons in 2013 to 615,992 tons in 2014 (KenInvest, 2016).